2011
DOI: 10.14742/ajet.932
|View full text |Cite
|
Sign up to set email alerts
|

Emphasising assessment 'as' learning by assessing wiki writing assignments collaboratively and publicly online

Abstract: <span>The use of Web 2.0 communication practices in assessment may offer a new approach to assessment 'as' learning, a goal for assessment that is more highly valued than assessment 'of' and even 'for' learning in the literature. This paper describes a case study of a wiki-writing assignment that aimed to achieve this goal. The stakes were high, in that the assignment was worth 100% of the mark and the assignment was set for a group of tertiary teachers who were enrolled in a unit of study about student … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 10 publications
2
15
0
Order By: Relevance
“…Submitting their work to Wikipedia allows their work to bring benefit to—and be improved upon—by the entire world. Although some students initially may be apprehensive about their work being in the public domain, most come to appreciate this aspect of their work (Davies, Pantzopoulos, & Gray, ). This echoes past research that has repeatedly shown that students are more motivated to participate in activities they see as having a visible impact on the real world (Hollis, ; Weigert, ).…”
Section: Increasing Students Motivation: Editing With Wikipedia Is Funmentioning
confidence: 99%
“…Submitting their work to Wikipedia allows their work to bring benefit to—and be improved upon—by the entire world. Although some students initially may be apprehensive about their work being in the public domain, most come to appreciate this aspect of their work (Davies, Pantzopoulos, & Gray, ). This echoes past research that has repeatedly shown that students are more motivated to participate in activities they see as having a visible impact on the real world (Hollis, ; Weigert, ).…”
Section: Increasing Students Motivation: Editing With Wikipedia Is Funmentioning
confidence: 99%
“…The same way, research of Cheng, Wu, and Liu (2015) that study correlation between perception of assessment task and classroom assessment environment (learning-oriented assessment environment, performance-oriented assessment environment) [8]. The result study Cheng, Wu, and Liu (2015) show that congruence with planned learning and student consultation are positive predictor of learning-oriented assessment environment and negative predictor of performanceoriented assessment environment [8]. Whiles no reports of relationships between perception towards assessment (it's means assessment of learning, assessment for learning, and assessment as learning) with learning result.…”
Section: Introductionmentioning
confidence: 86%
“…Alkharusi (2013) report that albeit not correlation causality between perceptions of assessment task (congruence with planned learning, authenticity, student consultation, transparancy, diversity) with motivation and learning, but this result study can help to understand how do silent aspects of assessment task related meaningfull towards motivation and learning [7]. The same way, research of Cheng, Wu, and Liu (2015) that study correlation between perception of assessment task and classroom assessment environment (learning-oriented assessment environment, performance-oriented assessment environment) [8]. The result study Cheng, Wu, and Liu (2015) show that congruence with planned learning and student consultation are positive predictor of learning-oriented assessment environment and negative predictor of performanceoriented assessment environment [8].…”
Section: Introductionmentioning
confidence: 99%
“…The most highlighted advantage of wikis as an educational tool is their capacity to engage students in collaborative learning. Wikis can facilitate a wide variety of authentic, collaborative and reflective learning activities (Davies, Pantzopoulos, & Gray, 2011). Within this context students become both author and audience, enabling a deeper level of interpretation to occur.…”
Section: Background and Rationalementioning
confidence: 99%